2021
DOI: 10.1017/s1754470x21000313
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a culturally adapted CBT-based online programme for depression and anxiety from a lower middle-income country

Abstract: Online cognitive behaviour therapy (CBT), self-help and guided self-help (GSH) interventions have been found to be efficacious and cost-effective for treatment of anxiety and depression, but there are limited data from low- and middle-income countries on culturally adapted digital interventions for these common mental disorders. The aim of this study was to investigate the feasibility and acceptability of an online culturally adapted CBT-based guided self-help (CaCBT-GSH) for patients with anxiety and depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…These findings suggest these skills can be effectively taught remotely to improve daily functioning for AYA in Zambia. Overall, these findings align with a growing body of literature supporting the use of telehealth care delivery ( 20 ), with less cost for both patients and clinicians compared to traditional visits ( 20 ).…”
Section: Discussionsupporting
confidence: 81%
“…These findings suggest these skills can be effectively taught remotely to improve daily functioning for AYA in Zambia. Overall, these findings align with a growing body of literature supporting the use of telehealth care delivery ( 20 ), with less cost for both patients and clinicians compared to traditional visits ( 20 ).…”
Section: Discussionsupporting
confidence: 81%
“…Next, 53 full texts on digital interventions were examined from the living Metapsy database and three more studies were identified through reference tracking. All full texts were screened against our current eligibility criteria resulting in 21 RCTs for inclusion in the present meta-analysis (Figure 1; Mogoaşe et al, 2013; Tulbure et al, 2015; Yeung et al, 2017; Arjadi et al, 2018; Ciuca et al, 2018; Karbasi and Haratian, 2018; Yeung et al, 2018; Moeini et al, 2019; Jannati et al, 2020; Salamanca-Sanabria et al, 2020; Wang et al, 2020; Araya et al, 2021; Ghosh et al, 2023; Heim et al, 2021; Latif et al, 2021; Newman et al, 2021; Sun et al, 2021; Cuijpers et al, 2022; Zhao et al, 2022).
Figure 1. Flow chart of the studies selection process.
…”
Section: Resultsmentioning
confidence: 99%